Without Consent : Mass-Elite Linkages in Presidential Politics - Miller, Warren E. (Warren Edward), 1924-1999 (Book collections on Project MUSE., 1988)
The transmission of policy preferences from the mass electorate to the political elite is the subject of Warren Miller's illuminating new book. The elites of whom he writes are the delegates to recent nominating conventions analyzed in their subsequent roles as activists involved in presidential election campaigns. Miller's analysis delineates circumstances and conditions that affect the degree to which the issue preferences of these elite activists are more or less representative of those held by rank-and-file members of the nation's electorate. Miller argues that, although consent and account.